Lithium battery ternary positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611103438.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的在于提供一种锂电池三元正极材料,以解决现有技术中锶掺杂制备工艺复杂、能耗高和批次稳定性差的问题
1.本发明通过采用SrO和/或Sr(OH)2作为体相掺杂锶源、Al2SrO4作为表面包覆原料,利用两者在烧结过程中的热力学行为差异,实现了先体相掺杂、后表面包覆的有序构建。具体而言,在低温预烧结阶段,SrO和/或Sr(OH)2分解生成的SrO开始获得足够能量,Sr2+离子逐渐从前驱体颗粒表面向颗粒内部晶格扩散,进入三元材料晶格取代Li位或过渡金属位,起到晶格柱撑作用,稳定层状结构;在高温固相烧结阶段,Sr2+扩散速率急剧增加,完成体相内的均匀分布,同时Al2SrO4在这一阶段与材料表面富集的残余锂化合物发生原位固相反应,生成具有快离子导体特性的Sr-Al-O复合层,既不阻碍锂离子脱嵌,又能完全隔绝材料与电解液的直接接触,抑制HF腐蚀与副反应。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a ternary cathode material for lithium batteries, its preparation method, and its application. Background Technology
[0002] With the rapid development of portable electronic devices, electric vehicles, and energy storage systems, the market has placed higher demands on the energy density, cycle life, safety, and production cost of lithium-ion batteries. Lithium nickel cobalt manganese oxide (NCM) ternary cathode materials, by adjusting the ratio of nickel, cobalt, and manganese, can balance high specific capacity and operational stability, and have become one of the core cathode materials for power lithium-ion batteries. Among them, medium-nickel 6-series materials (Ni content around 0.6%) have attracted widespread attention due to their good balance between energy density and safety.
[0003] However, existing technologies for the preparation and modification of ternary cathode materials still face several challenges. On one hand, high-temperature sintering is commonly used in the industry to improve material cycle stability and processing performance. However, high-temperature sintering leads to severe lithium volatilization, high energy consumption, and poor batch stability. Conversely, lowering the sintering temperature results in incomplete solid-phase reactions, poor material uniformity, and deterioration of electrochemical performance. On the other hand, element doping is the mainstream modification method for ternary materials. Strontium is widely used due to its excellent fluxing and modification effects, but existing strontium doping technologies have significant drawbacks: existing processes often employ two-step calcination or multi-step coating processes, resulting in long processes, high energy consumption, and the need for re-crushing after secondary calcination, which can easily lead to excessive fine powder, affecting electrode processing performance and battery cycle stability. Furthermore, existing technologies typically involve stepwise doping and coating, making it difficult to achieve synergistic optimization of bulk structure and surface interface during the same sintering process. Additionally, existing methods have limited control over the sintering atmosphere, failing to effectively suppress high-temperature side reactions for medium-nickel 6-series NCM materials, making it difficult to guarantee material performance consistency.
[0004] Therefore, there is an urgent need for a ternary cathode material that can solve the problems of complex preparation process, high energy consumption, and poor batch stability of strontium-doped ternary cathode materials in existing technologies, as well as the inability of nickel 6-series NCM materials to simultaneously achieve high specific capacity, long cycle stability and excellent processing performance under a simple process. Summary of the Invention
[0005] The purpose of this invention is to provide a ternary cathode material for lithium batteries to solve the problems of complex preparation process, high energy consumption and poor batch stability of strontium doping in the prior art.
[0006] The present invention also aims to provide a preparation method for preparing a lithium battery ternary cathode material with high specific capacity, long cycle stability, and low cation disorder.
[0007] The present invention also aims to provide an application of a ternary cathode material for lithium batteries in lithium-ion batteries.
[0008] In a first aspect, this invention discloses a ternary cathode material for lithium batteries, the general chemical formula of which is Li. 1.04 Ni 0.65 Co 0.15 Mn 0.20 Sr x O2, where x is the molar doping coefficient of Sr element in Sr source, x=0.0012~0.0024, corresponding to a doping amount of Sr element of 1000~2000ppm of the ternary precursor mass; The ternary precursor is Ni. 0.65 Co 0.15 Mn 0.20 Hydroxides of (OH)₂; The surface of the cathode material has an Sr-Al-O coating layer.
[0009] By adopting the above technical solutions, a fixed Li / Me ratio of 1.04 can precisely match the sintering characteristics of the medium-nickel NCM65 system, avoiding both excessive surface free alkali caused by lithium excess and lithium-nickel cation mixing problems caused by insufficient lithium; the Sr doping amount is precisely controlled within the range of 1000–2000 ppm, at which Sr 2+ It can fully diffuse into the bulk lattice of the material, and with its large ionic radius, it acts as a lattice pillar, suppressing the collapse and phase transformation of the layered structure during charge-discharge cycling. It can also reduce the activation energy of solid-state reactions, achieving a high degree of single crystallization at mild temperatures. Furthermore, below 1000 ppm, Sr... 2+ The lattice pillar effect is insufficient, making it difficult to effectively suppress the collapse of the layered structure during cycling; at concentrations above 2000 ppm, excess Sr... 2+ Capacity loss may occur due to the occupation of lithium sites, while an excessively thick surface coating can hinder lithium-ion diffusion. However, by combining a surface Sr-Al-O coating, direct contact between the electrolyte and the bulk material phase can be isolated without hindering lithium-ion insertion / extraction, thus suppressing HF corrosion and interfacial side reactions. The bulk doping and surface coating create a synergistic effect, simultaneously improving both the material's structural stability and interfacial compatibility.
[0010] Preferably, the D50 particle size of the ternary precursor is 3.0–4.0 μm, and the tap density is ≥1.8 g / cm³. 3 Its specific surface area is 8.0–12.0 m². 2 / g.
[0011] Preferably, the D50 particle size of the cathode material powder is 5.0–6.0 μm, and the specific surface area is 0.4–0.6 m². 2 / g, compacted density ≥3.65g / cm³ 3 .
[0012] Preferably, the Sr source includes SrO and / or Sr(OH)2.
[0013] Preferably, the raw material for the Sr-Al-O coating layer is Al2SrO4.
[0014] Preferably, the amount of Al2SrO4 added is 0.01% to 0.2% of the mass of the ternary precursor.
[0015] Preferably, the molar ratio of lithium in the cathode material to the total nickel, cobalt, and manganese metal elements in the ternary precursor is 1.04; Preferably, the lithium element is derived from lithium sources including Li2CO3 and LiOH.
[0016] Secondly, this invention also discloses a method for preparing a ternary cathode material for lithium batteries, comprising the following steps: S1. The ternary precursor, lithium source, Sr source and Al2SrO4 are mixed in a segmented dry process to obtain a uniformly mixed powder. S2. Place the mixed powder in the sintering equipment and perform two-stage one-time sintering. After sintering, cool it with the furnace to obtain sintered block material. S3. The sintered agglomerate is subjected to low-temperature pulverization and sieving to obtain Li. 1.04 Ni 0.65 Co 0.15 Mn 0.20 Sr x O2.
[0017] Preferably, in step S1, the dry mixing includes mixing at 300-500 rpm for 5-10 minutes, then mixing at 1000-1500 rpm for 20-30 minutes, and finally mixing at 600-800 rpm for 15-20 minutes.
[0018] Preferably, the two-stage single sintering process involves first uniformly heating to 500-600℃ for low-temperature pre-sintering, then uniformly heating to 920-940℃ for high-temperature solid-phase sintering, and finally uniformly cooling to below 200℃ before air cooling.
[0019] Preferably, a nitrogen-oxygen mixture with an oxygen concentration of 70% to 80% is introduced during low-temperature pre-sintering; high-purity oxygen with an oxygen concentration of ≥99.99% is introduced during high-temperature solid-phase sintering, and the oxygen pressure inside the furnace is maintained at 50 to 100 Pa.
[0020] Preferably, the heating rate for low-temperature pre-sintering is 2–3 °C / min, and the isothermal sintering time is 2–3 h. Preferably, the heating rate of high-temperature solid-state sintering is 2-3℃ / min, and the isothermal sintering time is 10-12h; Preferably, the cooling rate is 1–2 °C / min.
[0021] Preferably, in step S3, the low-temperature pulverization temperature is ≤40℃; and sieving is performed using a 325-mesh sieve.
[0022] Thirdly, the present invention also discloses the application of a ternary cathode material for lithium batteries in lithium-ion batteries.
[0023] The beneficial effects of this invention are: 1. This invention utilizes SrO and / or Sr(OH)2 as the bulk strontium doping source and Al2SrO4 as the surface coating material, leveraging the difference in their thermodynamic behavior during sintering to achieve ordered construction through bulk doping followed by surface coating. Specifically, during the low-temperature pre-sintering stage, SrO generated from the decomposition of SrO and / or Sr(OH)2 begins to acquire sufficient energy, and Sr... 2+ Ions gradually diffuse from the surface of the precursor particles into the internal lattice, entering the ternary material lattice to replace Li sites or transition metal sites, acting as lattice pillars and stabilizing the layered structure; during the high-temperature solid-state sintering stage, Sr... 2+ The diffusion rate increases sharply, achieving uniform distribution within the bulk phase. Simultaneously, Al2SrO4 undergoes an in-situ solid-phase reaction with the residual lithium compounds enriched on the material surface during this stage, generating a Sr-Al-O composite layer with fast ion conductor properties. This layer neither hinders lithium ion insertion / extraction nor completely isolates the material from direct contact with the electrolyte, thus suppressing HF corrosion and side reactions.
[0024] 2. The segmented atmosphere control process employed in this invention uses a low to medium oxygen concentration of 70%–80% during the low-temperature pre-sintering stage to avoid excessive decomposition and volatilization of the lithium source, while providing a mild environment for the uniform diffusion of the Sr source; during the high-temperature solid-state sintering stage, high-purity oxygen is switched to effectively suppress Ni… 2+ The co-arrangement of oxide and lithium nickel cations ensures the orderliness of the layered structure while promoting the densification and continuous growth of the coating layer. This invention achieves bulk doping and surface coating simultaneously in a single sintering process, significantly reducing sintering energy consumption and avoiding the complexity and high energy consumption of step-by-step processes. At the same time, it achieves dual stability of the material's bulk structure and surface interface, greatly improving the material's compaction density, cycle stability, and high-temperature safety. Detailed Implementation
[0025] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0026] A ternary cathode material for lithium batteries, the general chemical formula of which is Li 1.04Ni 0.65 Co 0.15 Mn 0.20 Sr x O2, where x is the molar doping coefficient of Sr element in Sr source, x=0.0012~0.0024, corresponding to a doping amount of Sr element of 1000~2000ppm of the ternary precursor mass; The ternary precursor is Ni. 0.65 Co 0.15 Mn 0.20 Hydroxides of (OH)₂; The surface of the cathode material has an Sr-Al-O coating layer.
[0027] By adopting the above technical solutions, a fixed Li / Me ratio of 1.04 can precisely match the sintering characteristics of the medium-nickel NCM65 system, avoiding both excessive surface free alkali caused by lithium excess and lithium-nickel cation mixing problems caused by insufficient lithium; the Sr doping amount is precisely controlled within the range of 1000–2000 ppm, at which Sr 2+ It can fully diffuse into the bulk lattice of the material, and with its large ionic radius, it acts as a lattice pillar, suppressing the collapse and phase transformation of the layered structure during charge-discharge cycling. It can also reduce the activation energy of solid-state reactions, achieving a high degree of single crystallization at mild temperatures. Furthermore, below 1000 ppm, Sr... 2+ The lattice pillar effect is insufficient, making it difficult to effectively suppress the collapse of the layered structure during cycling; at concentrations above 2000 ppm, excess Sr... 2+ Capacity loss may occur due to the occupation of lithium sites, while an excessively thick surface coating can hinder lithium-ion diffusion. However, by combining a surface Sr-Al-O coating, direct contact between the electrolyte and the bulk material phase can be isolated without hindering lithium-ion insertion / extraction, thus suppressing HF corrosion and interfacial side reactions. The bulk doping and surface coating create a synergistic effect, simultaneously improving both the material's structural stability and interfacial compatibility.
[0028] In some embodiments, the D50 particle size of the ternary precursor is 3.0–4.0 μm, and the tap density is ≥1.8 g / cm³. 3 Its specific surface area is 8.0–12.0 m². 2 / g.
[0029] By adopting the above technical solutions, selecting ternary precursors with specific particle sizes and morphologies helps to achieve uniform solid-phase reactions. Precursor particles with a D50 particle size of 3.0–4.0 μm have a suitable specific surface area, ensuring sufficient contact with the lithium source and dopant source while avoiding agglomeration and uneven sintering caused by excessively fine powder. Tap density ≥ 1.8 g / cm³. 3Ensuring a dense internal structure of the precursor particles is beneficial for the uniformity of element diffusion during sintering. Specific surface area: 8.0–12.0 m². 2 / g provides sufficient reactive sites, enabling SrO to effectively diffuse from the surface of precursor particles to the interior during the low-temperature pre-sintering stage, while also providing sufficient attachment sites for the subsequent reaction of Al2SrO4 with residual lithium on the surface.
[0030] In some embodiments, the D50 particle size of the cathode material powder is 5.0–6.0 μm, and the specific surface area is 0.4–0.6 m². 2 / g, compacted density ≥3.65g / cm³ 3 .
[0031] In some embodiments, the Sr source includes SrO and / or Sr(OH)2; The raw material for the Sr-Al-O coating layer is Al2SrO4, and the amount of Al2SrO4 added is 0.01% to 0.2% of the mass of the ternary precursor.
[0032] By adopting the above technical solutions, this invention uses SrO and / or Sr(OH)2 as doping sources, characterized by moderate thermal stability, and the ability to decompose and release Sr during the low-temperature pre-sintering stage. 2+ The doping process is completed by entering the bulk lattice; while Al₂SrO₄, as the coating source, undergoes an in-situ solid-state reaction with the residual lithium compounds enriched on the material surface during the high-temperature solid-state sintering stage, generating an Sr-Al-O composite coating layer. The synergistic use of these two raw materials achieves an ordered construction process of first bulk doping and then surface coating in the same sintering process, avoiding the complexity and high energy consumption of step-by-step processes. Al₂SrO₄ simultaneously provides Al and Sr elements, and the fast-ion conductor phase formed in the surface reaction possesses both good lithium-ion conductivity and chemical stability.
[0033] In some embodiments, the molar ratio of lithium in the cathode material to the total nickel, cobalt, and manganese metal elements in the ternary precursor is 1.04. Lithium is derived from lithium sources including Li2CO3 and LiOH.
[0034] A method for preparing a ternary cathode material for lithium batteries includes the following steps: S1. The ternary precursor, lithium source, Sr source and Al2SrO4 are mixed in a segmented dry process to obtain a uniformly mixed powder. S2. Place the mixed powder in the sintering equipment and perform two-stage one-time sintering. After sintering, cool it with the furnace to obtain sintered block material. S3. The sintered agglomerate is subjected to low-temperature pulverization and sieving to obtain Li. 1.04 Ni 0.65 Co 0.15 Mn0.20 Sr x O2.
[0035] By adopting the above technical solution, this invention directly sintersects the doping source, coating source, and main raw material after a single mixing process. Through precise two-stage temperature and atmosphere control, bulk doping and surface coating are achieved in the same furnace batch. This method eliminates the complex process of secondary sintering and secondary crushing required by traditional two-step methods, significantly reducing production energy consumption. It also avoids the problem of excessive fine powder caused by secondary crushing, improving batch stability of materials. Dry mixing avoids the wastewater treatment costs of wet processes, making it more environmentally friendly and economical.
[0036] In some embodiments, in step S1, dry mixing includes mixing at 300-500 rpm for 5-10 min, then mixing at 1000-1500 rpm for 20-30 min, and finally mixing at 600-800 rpm for 15-20 min.
[0037] By adopting the above technical solutions, this process ensures that SrO particles are uniformly attached to the surface of the precursor to facilitate subsequent diffusion doping. At the same time, Al2SrO4 is uniformly distributed to fully contact and react with residual lithium on the surface at high temperature, which is a prerequisite for achieving orderly construction by first doping and then coating.
[0038] In some embodiments, a nitrogen-oxygen mixture with an oxygen concentration of 70% to 80% is introduced during low-temperature pre-sintering; high-purity oxygen with an oxygen concentration of ≥99.99% is introduced during high-temperature solid-phase sintering, and the oxygen pressure inside the furnace is maintained at 50 to 100 Pa.
[0039] By adopting the above technical solutions, segmented atmosphere control is the key process feature for achieving synergistic modification in this invention. The low-temperature pre-sintering stage uses a medium-low oxygen concentration of 70%–80% to suppress excessive decomposition and volatilization of the lithium source, while simultaneously promoting uniform decomposition of SrO and Sr... 2+ Initial diffusion provides a mild oxidizing environment; however, if the oxygen concentration is too high at this stage, it will exacerbate lithium volatilization and premature formation of the surface oxide layer, hindering Sr. 2+ Diffusion into the bulk phase. During the high-temperature solid-state sintering stage, high-purity oxygen is switched on, which effectively suppresses Ni diffusion under high oxygen partial pressure. 2+ Oxidized to Ni 3+ The resulting mixing of lithium and nickel cations ensures the orderliness of the layered structure; on the other hand, it promotes the in-situ reaction of Al2SrO4 with residual lithium on the surface, generating a continuous and dense Sr-Al-O coating layer. Maintaining a slight positive pressure of 50-100 Pa inside the furnace prevents external air from seeping in and ensures the stability of the high-purity oxygen environment.
[0040] In some embodiments, the two-stage single sintering specifically involves first heating the temperature at a constant rate to 500–600°C for low-temperature pre-sintering, then heating the temperature at a constant rate to 920–940°C for high-temperature solid-state sintering, and finally cooling the temperature at a constant rate to below 200°C after sintering and then air-cooling the product.
[0041] The heating rate for low-temperature pre-sintering is 2–3 °C / min, and the isothermal sintering time is 2–3 h. The heating rate for high-temperature solid-state sintering is 2–3 °C / min, and the isothermal sintering time is 10–12 h. The cooling rate is 1–2 °C / min.
[0042] By adopting the above technical solutions, the two-stage temperature regime and the aforementioned segmented atmosphere control form a complete and synergistic process system. The selection of the 500–600℃ low-temperature pre-sintering temperature window is based on SrO activation and Sr... 2+ The diffusion kinetics of Sr below 500℃ 2+ The diffusion rate is too slow, resulting in low doping efficiency; temperatures above 600℃ may prematurely trigger surface reactions, interfering with the doping sequence. A high-temperature sintering temperature of 920–940℃ is designed for medium-nickel 6-series materials: below 920℃, the solid-state reaction is incomplete, and crystal development is insufficient; above 940℃, lithium volatilization intensifies, and energy consumption increases. A heating rate of 2–3℃ / min ensures thermal uniformity and avoids localized overheating; a low-temperature pre-sintering time of 2–3 hours ensures Sr… 2+ Sufficient diffusion into the surface lattice; high-temperature holding time of 10–12 h allows for full crystal growth and a continuous, dense coating layer. Slow cooling at 1–2 °C / min helps retain lattice oxygen, reduces structural defects during cooling, and further reduces the degree of cation mixing.
[0043] In some embodiments, in step S3, the low-temperature pulverization temperature is ≤40℃; sieving is performed using a 325-mesh sieve.
[0044] By adopting the above technical solutions, controlling the temperature of low-temperature pulverization to ≤40℃ can avoid local overheating during the pulverization process, which could lead to damage to the coating layer or crystal structure. A 325-mesh sieve can effectively remove a small number of large agglomerates that may be generated during sintering, ensuring a narrow and consistent particle size distribution in the final product, which is beneficial for subsequent electrode coating processing.
[0045] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0046] Example Example 1: A ternary cathode material for lithium batteries was prepared by the following method: S1, weigh out an amount with a D50 of 3.5 μm and a tap density of 1.9 g / cm³.3 Specific surface area 10.0 m² 2 / g of Ni 0.65 Co 0.15 Mn 0.20 1000g of (OH)2 ternary precursor, 545.2g of battery-grade lithium carbonate (Li / Me molar ratio 1.04), 1.8g of SrO (corresponding to Sr doping amount of 1500ppm of the ternary precursor mass), and 1.6g of Al2SrO4 were placed in a high-speed mixer and mixed at 500rpm for 10min, 1500rpm for 30min, and 800rpm for 20min. S2. In the low-temperature pre-firing stage, a nitrogen-oxygen mixture with a 75% oxygen concentration is introduced, and the temperature is raised to 600℃ at 2.5℃ / min, and sintered at a constant temperature for 2.5h. The furnace pressure is 80Pa. In the high-temperature stage, 99.99% high-purity oxygen is introduced, and the temperature is raised to 930℃ at 2.5℃ / min for high-temperature solid-state sintering, and sintered at a constant temperature for 11h. The temperature is then lowered to 180℃ at 1.5℃ / min and air-cooled after removal from the furnace. S3. Low-temperature airflow pulverization controls the material temperature to 35℃, followed by 325-mesh sieve separation to obtain a ternary cathode material for lithium batteries, Li. 1.04 Ni 0.65 Co 0.15 Mn 0.20 Sr 0.0012 O2.
[0047] Example 2: A ternary cathode material for lithium batteries, differing from Example 1 only in that the Sr doping amount is 1000 ppm of the ternary precursor mass.
[0048] Example 3: A ternary cathode material for lithium batteries, differing from Example 1 only in that the Sr doping amount is 2000 ppm of the ternary precursor mass.
[0049] Comparative Example Comparative Example 1 is a ternary cathode material for lithium batteries, which differs from Example 1 only in that the SrO doping amount is 500 ppm of the ternary precursor mass.
[0050] Comparative Example 2 is a ternary cathode material for lithium batteries, which differs from Example 1 only in that it does not contain SrO.
[0051] Comparative Example 3 is a ternary cathode material for lithium batteries, which differs from Example 1 only in that the high-temperature solid-state sintering temperature is 850°C.
[0052] Comparative Example 4: A ternary cathode material for lithium batteries, which differs from Example 1 only in that Al2SrO4 is not added.
[0053] Performance testing: 1. Physical property testing: Powder particle size was tested using a laser particle size analyzer, BET specific surface area was tested using a specific surface area analyzer, and compaction density was tested using a powder compactor. The test results are shown in Table 1.
[0054] 2. Electrochemical Performance Testing: Using the ternary cathode materials prepared in the examples and comparative examples as the cathode active material, a cathode slurry was prepared by mixing the cathode active material, conductive agent (SP), and binder (PCDF) in a mass ratio of 95:5:5. This slurry was then applied to the cathode current collector to form the cathode. A lithium sheet was used as the anode, and a conventional rate-controlled electrolyte was selected. The cathode sheet, separator, lithium metal anode, and electrolyte were assembled into a button cell in an argon-protected glove box, and their electrochemical performance was tested. The test conditions were: a constant temperature environment of 25°C, a cutoff voltage of 3.0-4.45V, activation at a constant current of 0.1C (1C=180mA / g) for the first three cycles, followed by 100 cycles at 1C. The test results are shown in Table 2.
[0055] Table 1 Physical performance test results
[0056] Table 2 Electrochemical performance test results
[0057] As shown in Table 1, the D50 particle size distribution of Examples 1 to 3 is between 5.49 and 5.95 μm, and the specific surface area is controlled between 0.48 and 0.55 m². 2 / g, the compacted density all reached 3.65g / cm³. 3 The above-mentioned particles exhibit good regularity and density, which is beneficial for improving the processing performance and volumetric energy density of the electrode. In contrast, the particles in Comparative Examples 1 to 4 have smaller particle sizes, larger specific surface areas, and lower compaction densities, reflecting incomplete particle development or unstable surface structures.
[0058] As shown in Table 2, Example 3 exhibits the best overall performance, with an initial discharge specific capacity of 213.4 mAh / g, a first-cycle coulombic efficiency of 90.97%, an initial 1C discharge specific capacity of 192.4 mAh / g, and a capacity retention rate of 98.61% after 100 cycles, indicating significant advantages in structural and interfacial stability. Examples 1 and 2 also demonstrate excellent cycle stability and high capacity retention, both superior to all comparative examples. Comparative Example 1, due to insufficient Sr doping, failed to fully utilize the lattice pillar effect, resulting in decreased cycle performance; Comparative Example 2, lacking Sr doping, exhibited poor bulk structural stability; Comparative Example 3, due to its low sintering temperature and incomplete crystal development, suffered severe degradation in long-cycle performance; Comparative Example 4, without the introduction of an Al2SrO4 coating layer, experienced intensified interfacial side reactions, leading to significantly accelerated capacity decay.
[0059] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A ternary cathode material for lithium batteries, characterized in that, The general chemical formula of the cathode material is Li. 1.04 Ni 0.65 Co 0.15 Mn 0.20 Sr x O2, where x is the molar doping coefficient of Sr element in Sr source, x=0.0012~0.0024, corresponding to a doping amount of Sr element of 1000~2000ppm of the ternary precursor mass; The ternary precursor has the general chemical formula Ni. 0.65 Co 0.15 Mn 0.20 Hydroxides of (OH)₂; The surface of the cathode material has an Sr-Al-O coating layer.
2. The lithium battery ternary cathode material according to claim 1, characterized in that, The ternary precursor has a D50 particle size of 3.0–4.0 μm and a tap density ≥1.8 g / cm³. 3 Its specific surface area is 8.0–12.0 m². 2 / g.
3. The lithium battery ternary cathode material according to claim 1, characterized in that, The positive electrode material has a powder D50 particle size of 5.0–6.0 μm and a specific surface area of 0.4–0.6 m². 2 / g, compacted density ≥3.65g / cm³ 3 .
4. The lithium battery ternary cathode material according to claim 1, characterized in that, The Sr source includes SrO and / or Sr(OH)2; The raw material for the Sr-Al-O coating layer is Al2SrO4.
5. The lithium battery ternary cathode material according to claim 1, characterized in that, The molar ratio of lithium in the cathode material to the total nickel, cobalt, and manganese metals in the ternary precursor is 1.
04. The lithium element is derived from lithium sources including Li2CO3 and LiOH.
6. A method for preparing a ternary cathode material for lithium batteries as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. The ternary precursor, lithium source, Sr source and Al2SrO4 are mixed in a segmented dry process to obtain a uniformly mixed powder. S2. Place the mixed powder in the sintering equipment and perform two-stage one-time sintering. After sintering, cool it with the furnace to obtain sintered block material. S3. The sintered agglomerate is subjected to low-temperature pulverization and sieving to obtain Li. 1.04 Ni 0.65 Co 0.15 Mn 0.20 Sr x O2.
7. The preparation method according to claim 6, characterized in that, In step S2, the two-stage one-time sintering specifically involves first heating the temperature at a constant rate to 500-600°C for low-temperature pre-sintering, then heating the temperature at a constant rate to 920-940°C for high-temperature solid-phase sintering, and finally cooling the temperature at a constant rate to below 200°C after sintering and air cooling. The low-temperature pre-sintering process introduces a nitrogen-oxygen mixture with an oxygen concentration of 70%–80%. The high-temperature solid-phase sintering process introduces high-purity oxygen with an oxygen concentration of ≥99.99%, and the oxygen pressure inside the furnace is maintained at 50-100 Pa.
8. The preparation method according to claim 7, characterized in that, The heating rate for the low-temperature pre-sintering is 2-3℃ / min, and the isothermal sintering time is 2-3h. The heating rate of the high-temperature solid-state sintering is 2-3℃ / min, and the isothermal sintering time is 10-12h. The cooling rate is 1–2 °C / min.
9. The preparation method according to claim 6, characterized in that, In step S3, the low-temperature pulverization temperature is ≤40℃; the sieving is performed using a 325-mesh sieve.
10. A lithium-ion battery, characterized in that, It includes a positive electrode material, wherein the positive electrode material is the ternary positive electrode material for lithium batteries as described in any one of claims 1-5.
